Challenges to the Indo-Pacific Security Architecture: Emerging Role for India - Arvind Kumar
India should play an active role in seeking to address the challenges to the creation of a new and acceptable Indo-Pacific security architecture. Over the years, the aspirations and ambitions of India have grown. It has been acknowledged as a predominant power in South Asia, and an emerging power in the whole of Asia. Its desire to be a leading power in the Indian Ocean Rim cannot be questioned. However, India cannot shy away from assuming responsibilities and playing a more proactive and positive role, especially if it desires to be an influential player in Asianand world affairs. India’s strategic orientations need to be adjusted togo beyond the Indian Ocean region to the Pacific Rim.